The Intriguing Contribution of Hippocampal Long-Term Depression to Spatial Learning and Long-Term Memory - Stacho, Martin; Manahan-Vaughan, Denise (Frontiers in Behavioral Neuroscience, 2022)
Long-term potentiation (LTP) and long-term depression (LTD) comprise the principal cellular mechanisms that fulfill established criteria for the physiological correlates of learning and memory. Traditionally LTP, that increases synaptic weights, has been ascribed a prominent role in learning and memory whereas LTD, that decreases them, has often been relegated to the category of ‘counterpart to LTP’ that serves to prevent saturation of synapses. In contradiction of these assumptions, studies over the last several years have provided functional evidence for distinct roles of LTD in specific aspects of hippocampus-dependent associative learning and information encoding. Furthermore, evidence of the experience-dependent ‘pruning’ of excitatory synapses, the majority of which are located on dendritic spines, by means of LTD has been provided. In addition, reports exist of the temporal and physical restriction of LTP in dendritic compartments by means of LTD. Here, we discuss the role of LTD and LTP in experience-dependent information encoding based on empirical evidence derived from conjoint behavioral and electrophysiological studies conducted in behaving rodents. We pinpoint the close interrelation between structural modifications of dendritic spines and the occurrence of LTP and LTD. We report on findings that support that whereas LTP serves to acquire the general scheme of a spatial representation, LTD enables retention of content details. We argue that LTD contributes to learning by engaging in a functional interplay with LTP, rather than serving as its simple counterpart, or negator. We propose that similar spatial experiences that share elements of neuronal representations can be modified by means of LTD to enable pattern separation. Therewith, LTD plays a crucial role in the disambiguation of similar spatial representations and the prevention of generalization.